OVERVIEW ABOUT SENSE OF COMMUNITY IN DUMOR (DULUR MOJOKERTO) ART’S COMMUNITY - Amanda Chintya Desy; Maryam, Effy Wardati (PT. Antis International Publisher, 2025)
Objective: This study aims to understand the sense of community within the Dulur Mojokerto arts community. Method: The subjects of this study consist of 56 individuals who are members of the Dulur Mojokerto arts community. The research employs a descriptive quantitative method, using a sense of community scale adapted from the 24-item Sense of Community Index Version Two (SCI-2) developed by McMillan and Chavis. The SCI-2 is a self-reporting measurement tool comprising 24 questions, with each dimension of the sense of community being represented by 6 questions. These dimensions include membership, influence, integration and fulfillment of needs, and shared emotional connection. Results: Data analysis using descriptive analysis shows that 80% of community members possess a medium sense of community. Novelty: This study provides empirical data on the sense of community within an arts-based community in Indonesia, specifically the Dulur Mojokerto arts community, which has not been widely explored in previous research.